Performance analysis on telecommunication companies in malaysia with TOPSIS model - Lam Weng Hoe; Lam Weng Siew; Liew Kah Fai (Institute of Advanced Engineering and Science, 2019)
Emergence of telecommunication companies is springing up due to the high demand from the consumers. The invention of telecommunication has made the world more knowledgeable as information can be transmitted easily. Based on the past studies, telecommunication is not commonly investigated especially in financial management field. Thereore, this study aims to propose a conceptual framework to evaluate, compare and rank the financial performance of the listed telecommunication companies in Malaysia using TOPSIS model. Financial ratios are employed to examine the financial performance of the telecommunication companies. The data of this study consists of DIGI, MAXIS, AXIATA and TM which are listed telecommunication companies in Malaysia stock market. The results of this study show that DIGI achieves the first ranking, followed by MAXIS, AXIATA and TM within the study period of year 2011-2015. This study is significant because it helps to evaluate, compare and rank the financial performance of the listed telecommunication companies in Malaysia with the proposed conceptual framework based on TOPSIS model.